Mangrovomyia, a new genus of long-legged flies from Iranian mangroves (Diptera: Dolichopodidae: Hydrophorinae) - Grichanov, Igor Ya.; Gilasian, Ebrahim (Zootaxa, 2023)
The genus Mangrovomyia Grichanov et Gilasian gen. nov. is described from Iran, including two new species, M. naserzadehae Grichanov et Gilasian sp. nov. and M. mofidii Grichanov et Gilasian sp. nov. The new genus is believed to be most closely related to the genera Hydrophorus Fallén, Epithalassius Mik and Paraliptus Bezzi in the subfamily Hydrophorinae, differing in peculiar characters of body setation, antenna, wing and male genitalia. The most distinct synapomorphies appear to be the very short and thick arista-like stylus; trapezoidal postpedicel with oblique transverse furrow; frons, face and clypeus covered with numerous setae, and anterior half of mesonotum covered with a field of numerous short setae and devoid of strong bristles. Mangrovomyia mofidii sp. nov. differs from M. naserzadehae sp. nov. in femora yellow (vs. black), fore tibia with thick and golden-brown (vs. thin and black) apical spine-like setae, katepisternum entirely covered with numerous setae (vs. without setae), and other features. Mangrove habitats of the new species are briefly discussed.